Tipologi Filsafat Islam Post Ibnu Rusyd - Hambali, R. Yuli Ahmad (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2019)
This article presents an attempt to uncover evidence of philosophical traditions in the Islamic world that are agreed to